The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2169/internalmedicine.52.8323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination Therapy with Renin-Angiotensin System Inhibitors and Eicosapentaenoic Acid on IgA Nephropathy

Abstract: Objective The beneficial effects of renin-angiotensin-aldosterone system inhibitors (RASI) and the omega-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) on IgA nephropathy (IgAN) have been reported. However, it is unknown whether these agents have any synergistic interactions. Methods We divided 38 IgAN patients into two groups: an EPA group (n=18) treated with RASI plus EPA and a DILAZEP group (n=20) treated with RASI plus dilazep dihydrochloride. We analyzed the clinical and histological background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In addition, a significant decrease in hematuria was observed, which, however, remained unchanged in the control group. Similar results were reported by Japanese researchers who used purified EPA [ 18 ]. These findings indicated that ω-3 PUFAs could possibly improve IgAN-associated proteinuria, independent of the renin–angiotensin system.…”
Section: History Of Treatment Of Igan With ω-3 Pufassupporting
confidence: 90%
“…In addition, a significant decrease in hematuria was observed, which, however, remained unchanged in the control group. Similar results were reported by Japanese researchers who used purified EPA [ 18 ]. These findings indicated that ω-3 PUFAs could possibly improve IgAN-associated proteinuria, independent of the renin–angiotensin system.…”
Section: History Of Treatment Of Igan With ω-3 Pufassupporting
confidence: 90%
“…Although slowly progressive over decades, IgAN is not a benign disease. Since IgAN was first described over 40 years ago, patients with this disease have been treated with oral steroids [4] , [14] , [15] , steroid pulse therapy [5] , [6] , tonsillectomy [7] , [16] , [17] , renin-angiotensin aldosterone system inhibitors [18] [20] , eicosapentaenoic acid [21] , statins [22] and combinations of these agents [23] . Although these agents were found to improve short and intermediate term renal outcomes, less is known about very long term outcomes in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The current cumulative evidence showed that RASi had statistically significant effects in reducing proteinuria and protecting kidney function [13]. RASi was the fundamental for long-term treatment of progressive IgA nephropathy [14,15]. The KDIGO guidelines also suggest that IgA nephropathy patients with persistent proteinuria more than 1.0 g/d despite 3 to 6 months of supportive care, and an eGFR ≥ 50 ml/min per 1.73 m 2 accept glucocorticoids therapy [5].…”
Section: Discussionmentioning
confidence: 99%